Functional characterization of the second feedback loop in the circadian clock of the Antarctic krill Euphausia superba - Chiara Stefanelli; Davide Colaianni; Gabriella M. Mazzotta; Gabriele Sales; Cristiano Bertolucci; Bettina Meyer; Alberto Biscontin; Cristiano De Pittà (BMC Biology)
Abstract Background The Antarctic krill Euphausia superba is a keystone species in the Southern Ocean ecosystem. This crustacean has an ancestral clock whose main components have been identified and characterized in the past few years. However, the second feedback loop, modulating clock gene expression through two transcription factors, VRI and PDP1, has yet to be described. The presence of this second regulatory mechanism is suggested by the identification of its negative component, vrille, at the transcriptional level. Results Here, we describe the second feedback loop of krill by identifying the positive component, pdp1, and functionally characterizing both pdp1 and vrille. Starting from the online transcriptome database KrillDB2, we identified and cloned three putative pdp1 sequences which were subsequently analyzed for tissue expression and functional activity using luciferase assays, individually and in combination with two vrille isoforms. Among the pdp1 isoforms, Espdp1_3 displayed higher expression levels in relevant circadian districts than the other two. Furthermore, EsPDP1_3 and EsVRI_2 exhibited the expected positive and negative regulation of the V/P-box in our in vitro system. Finally, Espdp1_3 and Esvrille also showed rhythmic expression in light–dark cycles, supporting their involvement in the regulation of the main circadian clock of the Antarctic krill. Conclusions This study expands our knowledge about the molecular architecture of the Antarctic krill circadian clock by defining the components that take part in the modulation of clock expression, establishing a second feedback loop.